Analisis Gaya Kepemimpinan Kepala Desa Dalam Meningkatkan Produktivitas Kinerja Aparatur Pemerintah Desa - Sri Hadiningrum, Anita Simanungkali, Cindy Ayu Lestari, Feby Flora Sembiring,Rinnauli Saragih, Titin (Pusdikra Publishing, 2023)
Leadership style in an organization has a very important role in determining the success of achieving an organization’s goals. The research used is a type of qualitative research. The type of research used is descriptive research where the data collected is in the form of information, images, not numbers. This research uses a survey approach using qualitative analysis methods with reference to the data that has been collected. The results of the research found evidence that leadership style improves performance. Village officials are considered quite successful. This is supported by evidence in the form of; The Village Head’s Leadership Style has provided work guidelines to Village Apparatus and scheduled their work properly and correctly; The Village Head’s leadership style has shown a lot of concern for the welfare and needs of his Village Apparatus; The Village Head’s leadership style in dealing with Village Apparatus is always to make wise and wise decisions; The Village Head’s leadership style has encouraged Village Apparatus to excel in serving the community; and the Village Head’s Leadership Style has greatly influenced the perception of Village Apparatus to motivate, in order to provide effective performance.